O repasse cambial no contexto do regime de metas de inflação: a experiência brasileira de 1999 a 2015. - PEREIRA, Geylson Serra (2018)
This work deals with the transfer of exchange rate variations to price levels in Brazil in a context of flexible exchange rate and Inflation Target Regime (IMR), covering the period from 1999 to 2015. It seeks to investigate how the Broad Consumer Price Index (IPCA) responds to shocks in the interest rate and exchange rate, in order to identify which of the variables has the greatest significance to explain the variations in the IPCA. To do so, it reviews the empirical work carried out in the framework of the estimation of exchange rate transfers in Brazil in the period 1999/2000 until, at least, 2015. Additionally, an evaluation is made of the evolutionary dynamics of the central variables of this work (exchange rate, inflation and interest). Before, however, a theoretical revision on theories of inflation and exchange rate determination, as well as international experiences in the implementation of the regime, is undertaken. It is observed in the results of this work that the IPCA reacts more significantly to the shocks in the exchange rate than to the interest rate shocks. In addition, exchange rate shocks have a more durable persistence, compared to interest shocks, thus constituting the variable (among the two) that is most relevant for determining the IPCA in the observed period.